2018
DOI: 10.1021/acsphotonics.7b01491
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Epsilon-Near-Zero Mode to Gap Plasmon Mode for Flat-Top Wideband Perfect Light Absorption

Abstract: Epsilon-near-zero (ENZ) materials, when probed at or near wavelengths corresponding to their zero permittivity crossing points, have unique and interesting properties that can be exploited for enhancing nanoscale light−matter interactions. Here, we experimentally show that over an order of magnitude increase in the absorption band of a periodically patterned metal− dielectric−metal structure can be obtained by integrating an indium tin oxide (ITO) subwavelength nanolayer into the insulating dielectric gap regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The result is the enhancement of the normal electric-field component inside the film and the formation of an absorption peak in the spectrum 31 . Recently, a growing number of applications have been identified for ENZ materials, including structural color formation by metallic-network ENZ metamaterials 32 , enhanced absorption in thin-film photovoltaics 33 , record-efficient plasmonic photocatalysis for hydrogen production 34 , thermal radiation engineering 35 , and broadband perfect absorption in gap-plasmon metasurfaces 36 . So far, these phenomena have been discussed within the local approximation of the film’s dielectric constant, in which the relative permittivity depends only on the frequency, i.e., ε L (ω)= ε ′( ω ) + iε ′′( ω ).…”
Section: Introductionmentioning
confidence: 99%
“…The result is the enhancement of the normal electric-field component inside the film and the formation of an absorption peak in the spectrum 31 . Recently, a growing number of applications have been identified for ENZ materials, including structural color formation by metallic-network ENZ metamaterials 32 , enhanced absorption in thin-film photovoltaics 33 , record-efficient plasmonic photocatalysis for hydrogen production 34 , thermal radiation engineering 35 , and broadband perfect absorption in gap-plasmon metasurfaces 36 . So far, these phenomena have been discussed within the local approximation of the film’s dielectric constant, in which the relative permittivity depends only on the frequency, i.e., ε L (ω)= ε ′( ω ) + iε ′′( ω ).…”
Section: Introductionmentioning
confidence: 99%
“…The right figure in this panel shows a SEM image of the MPA. In panel (b), an Au/SiO 2 /TiN MIM MPA is shown in which a thin film of ITO is implemented for broadening the absorption bandwidth of the MPA and can also be used for tuning purposes [134]. In (c) the schematic and SEM images of an AZO-based metamaterial are presented [135].…”
Section: Active Mpas Based On Tcos Superconductors Ferroelectrics mentioning
confidence: 99%
“…Moreover, it has been recently shown that [schematic depicted in Fig. 2(b)] by encapsulating a thin film of ITO between the top patterned layer and the bottom reflector in an MIM metamaterial absorber, it is possible to tunably broaden the absorption bandwidth of the metamaterial around 1.5 μm [134]. The physics behind this broadness is due to the coupling of the epsilon-near-zero mode to the gap plasmon mode supported by the metamaterial.…”
Section: Active Mpas Based On Tcos Superconductors Ferroelectrics mentioning
confidence: 99%
“…Recently, a novel class of materials with zero or near-zero permittivity at one or multiple wavelengths, known as epsilon-near-zero (ENZ) material, has become a research focus in photonics [10]- [13]. It has been reported that ENZ materials exhibit many extraordinary optical properties, including tunneling effects [14], transmission with constant phase [15], field enhancement [16], strong coupling phenomena [17] and large nonlinear responses [18], [19], etc. The ENZ material can be obtained in natural semiconductors or artificial metamaterials.…”
Section: Introductionmentioning
confidence: 99%